The Influence of Human Resource Competence, Utilization of Information Technology, and Internal Control Systems on The Quality of Financial Report Public Health Center in The City of Surabaya - Purwandari, Aprilia; Widajantie, Tituk Diah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out how human resource competence, utilization of information technology, and internal control systems influence the quality of financial reports of Public Health Centers in the City of Surabaya. This research employs quantitative research methodology, and primary data were collected using a questionnaire as the major data gathering tool. The population used in this research were all employees of Public Health Centers in Surabaya City and sample selection was carried out using the Slovin formula and the results obtained were 97 employees who will be used in this research. This study uses basic random sampling as its sample method. The SmartPLS 4.0 tool is used in this study's data analysis methodology. The study's findings indicate that while internal control systems and HR competency has an influence on the quality of financial reports, meanwhile, the utilization of information technology has no influence on the quality of financial reports. The contribution of this research is in maintaining the quality of financial reports for community health centers in the city of Surabaya as well as providing a potential evaluation for improvement future.